Autoimmune pancreatitis: Characteristics on CT imaging - Yongpitayapong, Chinapoj; Vachiranubnap, Busakorn (Chulalongkorn Medical Journal, 2023)
Background : Autoimmune pancreatitis (AIP) is a rare disease, describes a form of chronic pancreatitis with associated autoimmune mechanism and difficulties in diagnosis. Focal AIP may mimic pancreatic cancer. Objective : The purpose of this study was to determine the possible CT findings of the patients with AIP. Design : Retrospective descriptive study. Setting : King Chulalongkorn Memorial Hospital. Materials and Methods : Retrospectively review of clinical presentations, laboratory data and CT findings with pancreatic protocol of 8 patients who were diagnosed with AIP between January 1st, 2000 and May 31st, 2012. Results : All patients presented with jaundice and elevated serum IgG4 level. CT findings: diffuse (1of 8 patients, 12.5%) or focal (4 of 8 patients, 50%) pancreatic enlargement, normal pancreatic parenchymal enhancement (1 of 8 patients, 12.5%), abnormal pancreatic parenchymal enhancement (7 of 8 patients, 87.5%), normal pancreas (3 of 8 patients, 37.5%), loss of normal pancreatic lobularity (3 of 8 patients, 37.5%), peripancreatic fat stranding (1 of 8 patients, 12.5%), positive “halo sign” (2 of 8 patients, 25%), diffuse pancreatic duct dilatation (2 of 8 patients, 25%), diffuse CBD dilatation with wall enhancement and thickening (2 of 8 patients, 25%), normal CBD with intrapancreatic bile duct dilatation with wall enhancement and thickening (1of 8 patients, 12.5%), diffuse CBD dilatation with stent insertion (3 of 8 patients, 37.5%), diffuse duct dilatation (1of 8 patients, 12.5%), normal CBD (1of 8 patients, 12.5%). Conclusion : CT findings of AIP showed classic appearances of diffuse pancreatic enlargement with loss of normal pancreatic lobularity, peripancreatic fat standing, and positive “halo” sign with pancreatic or CBD dilatation, or focal pancreatic enlargement. However, normal CT imaging of pancreasis one characteristic on CT imaging.